Traditional use of medicinal plants from the Caatinga in the treatment of intestinal worms (Acta Scientiarum. Biological Sciences, 2026)
The Caatinga biome has a flora of extensive economic potential and cultural significance for local communities, which use plant species as therapeutic and health care agents. In particular, intestinal parasites affect a large part of the traditional communities living in this biome. Because of this, many regional plants are used to manage the parasitic infections they cause. This study consists of a bibliographic review aiming to synthesize scientific knowledge on the traditional use of Caatinga plants in the management of intestinal worms, identifying the most promising species and the cultural significance of the medicinal use of plants in the region. A total of 49 species were identified, distributed across 27 families, and those most cited with traditional vermifuge use were Mexican tea (Chenopodium ambrosioides L.), purge potato (Operculina macrocarpa L.), aloe vera (Aloe vera L.), papaya (Carica papaya L.), and castor bean (Ricinus communis L.). The main parts of the plants used were the leaves, bark, and roots, and the medicinal preparations were mainly teas, decoctions, and infusions derived from plant extracts. The review also highlights the importance of this knowledge as cultural heritage for communities in the region, particularly Indigenous people, quilombolas, and rural families, as well as the significance of public policies for preserving the Caatinga flora.